Classification of hydrocarbons trapping systems of the Ghadames and Murzuq Basins in relation to Gargaf high, West Libya - Ahmed, Al Fasatw (Libyan Journal of Science &Technology, 2022)
The Ghadames and Murzuq Basins, West Libya, are major producers of hydrocarbons in Libya. The producing-bearing horizons of the two basins range in age from Cambro-Ordovician to Triassic. Reservoirs of Devonian and Silurian age are major producing horizons in the Ghadames Basin. In the Murzuq Basin, the main reservoirs are Cambro-Ordovician in age. The Silurian Tanezzuft shales are the main source rock of the hydrocarbons in the Ghadames and Murzuq Basins. The reservoir characteristics indicate that the hydrocarbons of the Ghadames basin have mainly accumulated mainly in combination and stratigraphic traps in areas close to Gargaf high, and in structural anticline traps in areas close to the centre of the basin. In the Murzuq Basin, hydrocarbons are trapped mainly in structural faulted traps. The distribution of oil fields in the Ghadames and Murzuq Basins appears to be confined to a regional trend, which reflects the close relationship between tectonics, sedimentation, oil migration and accumulation.